2020
DOI: 10.1186/s13063-020-04629-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of psychoeducational intervention, based on a self-regulation model on menstrual distress in adolescents: a protocol of a randomized controlled trial

Abstract: Introduction: Menstrual distress caused by primary dysmenorrhea is associated with physical and psychological symptoms-before, after, and during menstruation. Leventhal's self-regulation educational model is based on the cognitive and emotional experiences of threat responses to symptoms and relates to coping responses. This study aims to investigate the effect of the implementation of a psychoeducational intervention, based on the selfregulation model of menstrual distress in adolescents. Methods/design: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…It also seems that socio-cultural and geographical differences play a role in this difference (25, 30). Similar to the present study in other studies in Iran and other countries, dysmenorrhea has been reported as the most common menstrual disorder (36)(37)(38) and this rate in studies has varied from 56% to 82% (1, 6, 9, 11-13, 23, 32). Due to the effects of dysmenorrhea on students' poor performance in school, it is important to pay attention to its risk factors (9).…”
Section: Resultssupporting
confidence: 90%
“…It also seems that socio-cultural and geographical differences play a role in this difference (25, 30). Similar to the present study in other studies in Iran and other countries, dysmenorrhea has been reported as the most common menstrual disorder (36)(37)(38) and this rate in studies has varied from 56% to 82% (1, 6, 9, 11-13, 23, 32). Due to the effects of dysmenorrhea on students' poor performance in school, it is important to pay attention to its risk factors (9).…”
Section: Resultssupporting
confidence: 90%
“…(Bernardi et al, 2017) mention that there is a need for education on effective therapeutic interventions to improve the quality of life during the menstrual period. (Asgari et al, 2020) reports that the severity of menstrual symptoms can be reduced by psycho-educational interventions. As many young women suffer from discomfort during menstruation, it is hoped that more non-drug methods will be developed to reduce the symptoms.…”
Section: Menstrual Discomfort Symptoms and Relevant Factorsmentioning
confidence: 99%
“…Since every woman’s menstrual cycle starts from adolescence and it is easier to institutionalize healthy health behaviors at this age, and considering the significance of maintaining the health of adolescent girls and the harmful effects of PMS on the various functions of students, especially on their academic performance [ 4 ], as well as considering that there is a widespread gender inequality in medical research, which leads to a lack of research on menstrual problems and women’s health issues in general [ 13 , 14 ], the present study investigates the effect of educational intervention based on the Health Belief Model on the lifestyle related to premenstrual syndrome and reduction of its symptoms among the first-grade high school girls.…”
Section: Introductionmentioning
confidence: 99%